Numerical and experimental study of flow behaviours in porous structure of aluminium metal foam - Shikh Anuar, Fadhilah; Mohd Sa'at, Fatimah Al-Zahrah; Mat Tokit, Ernie; Narasimmanaidu, Satishwara Rao (Joint Journal of Novel Carbon Resource Sciences & Green Asia Strategy, 2021)
This study conducted a simulation and an experimental study on a channel that was partly filled with open-cell metal foam block. Different blockage ratios have been considered, where the foam height could occupy more than half of the channel size. The aim is to investigate the flow behaviours across the complicated structure of the porous medium. Results show that the use of Ergun and Forchheimer models showed a similar stagnant region and recirculation zone in the partially filled channel, which agreed with the experimental results. However, the deviation in pressure drop performance at a high blockage ratio is noticeable.